COMPUTERIZED ADMINISTRATIVE INFORMATION SYSTEM IN HOME OWNERSHIP UNIT PERUMNAS KARAWACI - Fx. Chrisbijantoro Fx. Chrisbijantoro; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 1996)
Computerization as an alternative to solving the problems faced by the old system is expected to help sales personnel affairs and financial affairs and administration in making the reports or output required by the current or recent results and is expected to also be able to improve the efficiency and effectiveness in terms of time and effort work. Data storage media in hard disks and floppy disks as a backup to save space and secure, while also can be used multiple times and also to simplify and accelerate the search for the necessary data and easy storage. process engine will provide results information with a very small possibility of error and can generate the proper reports or output, correct and update.